The Nearctic species of Asindulum Latreille and Macrorrhyncha Winnertz (Diptera: Keroplatidae) - Fitzgerald, Scott J. (Zootaxa, 2023)
The genera Asindulum Latreille and Macrorrhyncha Winnertz are revised for the Nearctic Region with six species recognized, four in Asindulum and two in Macrorrhyncha: Asindulum coxale Loew generic combination reinstated, A. flavidum n. sp., A. mexicanum n. sp., A. montanum Röder, Macrorrhyncha borealis n. sp., and M. vockerothi n. sp. Asindulum tenuipes Walker should be excluded from future keroplatid works as it belongs to the family Blephariceridae and previous Nearctic records of the Palearctic species Macrorrhyncha flava Winnertz are discussed and concluded to be based on misidentifications. Nearctic taxa are imaged and a key to the species of Asindulum and the Nearctic species of Macrorrhyncha is provided. The two Palearctic species of Asindulum, A. nigrum Latreille and A. theodori Matile, are briefly addressed in the text and the male terminalia of the first species imaged to allow for comparison with the very similar Nearctic species A. coxale.